Data Duped: How to Avoid Being Hoodwinked by Misinformation - Gibson, Derek W.; Camm, Jeffrey D. (Rowman & Littlefield Publishers, 2023)
Gives you the superpower to be a healthy skeptic when consuming data and information. Data Duped is a book about how we are commonly deceived by numbers in our everyday lives. From lotteries, product warranties, and weight loss fads to misleading headlines and social media posts, there is no shortage of confusing or misleading information. Numbers are used to manipulate our decisions and impact our lives in ways that may not be immediately apparent. Data Duped will help you avoid being fooled by these messages and to develop a sense of ‘data defense’ by learning what types of questions to ask and how to maintain a healthy level of curiosity and data skepticism. Data Duped guides readers to discern the differences between the plausible and the ridiculous along a journey of informed critical thinking and data literacy. With historical parallels alongside practical and relatable examples, readers will learn how to spot the ‘malarkey’ from the truth and how to avoid being hoodwinked by misinformation.